REFLECTION OF PEOPLE’S ORAL CREATION PATTERNS IN ABDURAUF FITRAT’S RESEARCH - Yakubova Zebuniso Yarkinjanovna (Galaxy International Interdisciplinary Research Journal, 2024)
Abdurauf, as a great scholar of Fitrat’s era, conducted research in all directions of literary studies. Fitrat, as a textologist, source scholar, linguist, lexicographer, literary critic, and theoretician, created a number of scientific treatises and articles, and most of the scientific conclusions reflected in this scientific heritage serve as the basis for today’s research. Through this article, we will get acquainted with his thoughts and literary classifications related to literary studies and examples of folk oral creativity in his researches.